KAJIAN KONSISTENSI SIKAP DAN PERBUATAN BERBAHASA INDONESIA BIDANG KEILMUAN - Marsudi; Siti Zahrok (Institut Teknologi Sepuluh Nopember, 2017)
Attitude can be defined as permanent sense, thought, and preference on specificaspect of life. In fact, language attitude of speakers of Bahasa Indonesia isinteresting to be questioned. In relation to this, the aim of this research is todescribe consistency in terms of language attitude and language performanceamong Bahasa Indonesia users. Positive thought and sense toward BahasaIndonesia should be completely or at least partly actualized on the use ofstandard language when it is implemented in academic setting. In this articleused the approach of qualitative methods, namely the object of study in thisarticle has a natural character. This approach is expected to find thephenomena and social problems that occur in the object of study. Cases foundin the use of Bahasa Indonesia tend to oppose the essence of language attitudeInconsistency among bahasa Indonesia attitude lies on the level of spelling,diction, and sentence structures The causes of this inconsistency rest on thedisparage and ignorance of Bahasa Indonesia language principles The use ofBahasa Indonesia ignoring language principles particularly on academicsetting is viewed as unimportant and unurgent matter. Therefore, negativeattitude emerges as a result of ignored language principles